2014
DOI: 10.1371/journal.pone.0095937
|View full text |Cite
|
Sign up to set email alerts
|

Does Mortality Risk of Cigarette Smoking Depend on Serum Concentrations of Persistent Organic Pollutants? Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) Study

Abstract: Cigarette smoking is an important cause of preventable death globally, but associations between smoking and mortality vary substantially across country and calendar time. Although methodological biases have been discussed, it is biologically plausible that persistent organic pollutants (POPs) like polychlorinated biphenyls (PCBs) and organochlorine (OC) pesticides can affect this association. This study was performed to evaluate if associations of cigarette smoking with mortality were modified by serum concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…We could not confirm previous observations that obesity 24 or smoking 44 modify the association of POPs with mortality. However, we did find evidence for nonlinear associations of PCBs 206, 189, and 99 with all-cause mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…We could not confirm previous observations that obesity 24 or smoking 44 modify the association of POPs with mortality. However, we did find evidence for nonlinear associations of PCBs 206, 189, and 99 with all-cause mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…This study found that among participants with relatively high POPs, former or current smokers had a higher risk of mortality than the never-smokers ( 14 ). The same research group further confirmed this interaction in another cohort of 70-year old participants in Sweden ( 13 ). However, the mechanisms responsible for this interaction effect have not been elucidated.…”
Section: Discussionmentioning
confidence: 62%
“…Smoking is a well-known risk factor for hypertension. Previous studies reported an interaction effect between smoking and persistent organic pollutants (POPs), PCBs, or organochlorine pesticides on mortality ( 13 , 14 ), indicating that smoking may modify the association between pesticides exposure and hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking status was defined based on self-report and categorized into current, former and never smokers (30). Plasma samples were stored at -70°C until analysis and transported between the participating centres on dry ice.…”
Section: Methodsmentioning
confidence: 99%
“…BMI was defined as body weight in kilograms divided by the squared body height in meters and was based on measurements performed at the enrolment. Smoking status was defined based on the self-report and categorized into current, former and never-smokers ( 30 ). Plasma samples were stored at −70°C until analysis and transported between the participating centere on dry ice.…”
Section: Methodsmentioning
confidence: 99%